OVERCOMING TERRORISM THREATS IN AIR FORCE BASE : CASE STUDY OF HALIM PERDANAKUSUMA AIR FORCE BASE - Sony Aji Pramono; Arfin Sudirman; Yusa Djuyandi (Universitas Padjadjaran, 2022)
ABSTRACT: Terrorism is one form of transnational crime and is very threatening tranquility and peace. In Indonesia, terrorism crimes often occur and consume victims that are not small in number from their own citizens or from foreign nationals. The purpose of the study